2022
DOI: 10.3389/fnmol.2022.974890
|View full text |Cite
|
Sign up to set email alerts
|

More than a marker: potential pathogenic functions of MAP2

Abstract: Microtubule-associated protein 2 (MAP2) is the predominant cytoskeletal regulator within neuronal dendrites, abundant and specific enough to serve as a robust somatodendritic marker. It influences microtubule dynamics and microtubule/actin interactions to control neurite outgrowth and synaptic functions, similarly to the closely related MAP Tau. Though pathology of Tau has been well appreciated in the context of neurodegenerative disorders, the consequences of pathologically dysregulated MAP2 have been little … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 181 publications
1
20
0
Order By: Relevance
“…NFTs accumulate in the entorhinal cortex, the subiculum, and in CA1 of the hippocampal region, 1,2 in the control cases, demonstrating age‐related neuropathological changes. Although the rate of p‐tau accumulation and the degree of destabilization of MAP2 occur independently, 29 it is thought that as NFTs increase, MAP2 destabilizes, the neurons lose plasticity, and neuronal atrophy will follow 18 . Here we assessed the change in the number of MAP2‐positive neurons in the hippocampus and entorhinal cortex.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NFTs accumulate in the entorhinal cortex, the subiculum, and in CA1 of the hippocampal region, 1,2 in the control cases, demonstrating age‐related neuropathological changes. Although the rate of p‐tau accumulation and the degree of destabilization of MAP2 occur independently, 29 it is thought that as NFTs increase, MAP2 destabilizes, the neurons lose plasticity, and neuronal atrophy will follow 18 . Here we assessed the change in the number of MAP2‐positive neurons in the hippocampus and entorhinal cortex.…”
Section: Resultsmentioning
confidence: 99%
“…The microtubule‐associated proteins (MAPs) of type II (MAP2) stabilize the dendrites and the axons of neurons. Studies show that p‐tau is mislocated to dendritic spines leading to microtubule destabilization and synaptic dysfunction 17–20 . In addition, synaptic loss is reported to be associated with microglia‐mediated neuroinflammation in AD 21,22 …”
Section: Introductionmentioning
confidence: 99%
“…Lastly, mature neurons are characterized by the expression of microtubule-associated protein 2 (MAP2), which stabilizes microtubules in the dendrites, and RNA binding fox-1 homolog 3 (RBFOX3), a neural-specific pre-mRNA alternative splicing regulator that also produces the widely used neuronal nuclei antigen ( 61 , 62 ). As with the expression of TUBB3 , the expression of both MAP2 and RBFOX3 was significantly increased in cells encapsulated within both DYN gels compared to those in Static gels (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The quantitative results of residual brain volume showed that compared with Sham group, the brain atrophy was obvious in HI group, and myricetin treatment could significantly alleviate the degree of brain atrophy in HI-induced rats ( Figure 2B ). Microtubule-associated protein-2 (MAP-2) is the main cytoskeletal regulator within neuronal dendrites that serves as a robust somatodendritic marker ( DeGiosio et al, 2022 ). Myelin basic protein (MBP) is a key component of myelin sheath in the central nervous system that serves as an oligodendrocyte marker ( Harauz et al, 2004 ).…”
Section: Resultsmentioning
confidence: 99%